Bim adoption framework to enhance efficiency of contractual issues in the jordanian construction sector - Ibrahim Moh'd Abdel, Qader Saraireh (2022)
Construction contracts are becoming more challenging these days with the rise of complexity in design, competitive profit margins, diverse requirements and the emergence of many disruptive technologies. Additionally, the construction contracts require extensive information and documentation to be successfully managed. Ineffective strategy and management often lead to disputes between the stakeholders. In Jordan, many contractual problems affect the contract administration. Thus, it weakened the construction industry's contribution to Growth Domestic Product (GDP) in recent years. The contractual problems are costly and time-consuming to resolve. Many researchers have documented Building Information Modelling (BIM) as a considerably efficient approach to reduce the contractual problems in the projects. It lies on the capability of BIM to integrate information, centralize communication, improve understandings of designs through virtual 3D and resolve conflict virtually before the physical activities take place. Despite many benefits, the implementation of BIM, however, requires an appropriate regulatory framework to succeed. Therefore, this study fills the research gap by developing a conceptual framework for adopting BIM to improve the efficiency of the contractual issues in the construction sector in Jordan. A mixed-method of data collection was adopted to achieve the research’s objectives. It included interviews with 27 experts, 410 completed questionnaires surveys and 25 experts participated in the focus group validation workshop. The data collected from the interviews & workshop were analyzed by using the content analysis technique. Questionnaire responses were analyzed descriptively and statistically using SPSS software. The results from the interviews show that the major contractual issues contributed from problems related to the tender documents (contracts, drawings), contractual parties, arbitration and disputes resolution, problems related to technology use, financial problems and administrative problems. On the other hand, the results from the questionnaire confirmed that the significant barriers to BIM adoption include the lack of BIM awareness with an RII score of 0.736, lack of BIM training centres with an RII score of 0.724 and lack of support from the government with an RII score of 0.700. Furthermore, the findings of questionnaires assured that the main benefits of BIM adoption are as-built drawings with an RII score of 0.828, data sharing among parties with an RII score of 0.766, clash detection with an RII score of 0.760. In addition, improving the design with an RII score of 0.756 and save cost and time with an RII score of 0.756. This research highlighted the critical contractual problems during the project life cycle. Moreover, the study offers a conceptual framework for BIM adoption as a viable solution to overcome the contractual issues, and the barriers of BIM adoption, which will ultimately boost the performance of the Jordanian construction sector.